2021
DOI: 10.3390/ani11020295
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of the Secretome and Exosomes of Feline Adipose-Derived Mesenchymal Stem Cells

Abstract: Mesenchymal stem cells (MSCs) have been shown to have therapeutic efficacy in different complex pathologies in feline species. This effect is attributed to the secretion of a wide variety of bioactive molecules and extracellular vesicles, such as exosomes, with significant paracrine activity, encompassed under the concept of the secretome. However, at present, the exosomes from feline MSCs have not yet been studied in detail. The objective of this study is to analyze and compare the protein profiles of the sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 72 publications
1
9
0
Order By: Relevance
“…The chemokine RANTES participates in the regulation of perivascular inflammation, vascular malfunction, and T-cell accumulation in cardiovascular disease [ 53 ]. Recently, exosomes and secretomes were separated from feline AD-MSCs, and proteomics KEGG and GO analyses were conducted to address the possibility of using exosomes as therapeutic substances [ 54 ]. Several studies reported the analysis and characterization of exosomes derived from canine-species MSCs and presented differential expression of cytokines and growth factors in adipose tissue- and bone-marrow-derived MSC exosomes [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…The chemokine RANTES participates in the regulation of perivascular inflammation, vascular malfunction, and T-cell accumulation in cardiovascular disease [ 53 ]. Recently, exosomes and secretomes were separated from feline AD-MSCs, and proteomics KEGG and GO analyses were conducted to address the possibility of using exosomes as therapeutic substances [ 54 ]. Several studies reported the analysis and characterization of exosomes derived from canine-species MSCs and presented differential expression of cytokines and growth factors in adipose tissue- and bone-marrow-derived MSC exosomes [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, fAd-MSCs of each donor were isolated and characterized according to a protocol previously optimized within our group [ 15 , 29 ]. Briefly, adipose tissue was treated with type I collagenase (Merck, Darmstadt, Germany) and the isolated fractions were seeded in T-175 culture flasks containing DMEM supplemented with 10% fetal bovine serum (FBS), 2.5 mM L-glutamine, 100 U/mL penicillin, 100 µg/mL streptomycin, and 1.25 µg/mL fungizone (Merck, Darmstadt, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…The exosomes from each individual donor were processed separately. The isolation of the exosomes was conducted by ultracentrifugation and their characterization afterwards was conducted following a protocol previously used by our group [ 13 , 15 ]. Briefly, the cells of each donor were seeded at a density of 5.7 × 103 cells/cm 2 in three T-175 flasks in DMEM supplemented with 10% fetal bovine serum (FBS), 2.5 mM L-glutamine, 100 U/mL penicillin, and 100 µg/mL streptomycin (Merck, Darmstadt, Germany).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is currently assumed that the mechanism of action of the MSCs to maintain homeostasis and to modulate the responses of the immune system is mainly paracrine and relies on the production and release of a great variety of biomolecules with different biological functions. Altogether, these components secreted by the cells, which include growth factors, cytokines, and extracellular vesicles, among others, are known as the secretome [11][12][13]. In some human pathologies, such as lupus, type 2 diabetes, or metabolic syndrome, it has been shown that the MSCs of the patients are dysfunctional and may participate in the etiopathogenesis of the diseases [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%